IoT-Based Automatic Home Light Monitoring System Using Wemos D1 Mini - Utari; Lukman Hakim (Talenta Publisher, 2022)
This research aims to design an IoT-based home light monitoring system using Wemos D1 Mini. This tool is designed to control the current and voltage contained in house lights automatically. The sensor used to measure the current in the house lights is the ACS712 sensor, and the sensor used to measure the voltage in the house lights is the ZMPT101B sensor. The simulation of the house lights on this tool uses three LED lights, where each lamp is located on the terrace of the house, living room, and kitchen with different light power variations. In addition, the Blynk application on smartphones can be used to turn lights off and on and monitor currents and voltages. The test results show that this tool can control three regulated room lights and monitor the current and voltage in the three lights online using the Blynk application.